Identification of HDAC9 as a viable therapeutic target for the treatment of gastric cancer - Xiong, Kai (Exp Mol Med, 2019)
Histone deacetylase inhibitors (HDACis) are a new class of anticancer drugs confirmed to have good therapeutic effects against gastric cancer (GC) in preclinical experiments, but most HDACis are non-selective (pan-HDACis), with highly toxic side effects. Therefore, it is necessary to screen HDAC family members that play key roles in GC as therapeutic targets to reduce toxic side effects. In this study, we evaluated the targeting specificity of the HDACi suberoylanilide hydroxamic acid (SAHA) for GC via fluorescence molecular imaging (FMI). In vitro FMI results showed that SAHA had higher binding affinity for GC cells than for normal gastric cells. In vivo FMI of gastric tumor-bearing mice confirmed that SAHA can be enriched in GC tissues. However, there was also a high-concentration distribution in normal organs such as the stomach and lungs, suggesting potential side effects. In addition, we found that among the HDAC family members, HDAC9 was the most significantly upregulated in GC cells, and we verified this upregulation in GC tissues. Further experiments confirmed that knockdown of HDAC9 inhibits cell growth, reduces colony formation, and induces apoptosis and cell cycle arrest. These results suggest that HDAC9 has an oncogenic role in GC. Moreover, HDAC9 siRNA suppressed GC tumor growth and enhanced the antitumor efficacy of cisplatin in GC treatment by inhibiting the proliferation and inducing the apoptosis of GC cells in vitro and in vivo. Our findings suggest that the development of HDAC9-selective HDACis is a potential approach to improve the efficacy of chemotherapy and reduce systemic toxicity.